A Novel Technique for Closed Reduction and Fixation of Paediatric Calcaneal Fracture Dislocation Injuries - Radwane Faroug; Paul Stirling; Farhan Ali (Case Reports in Orthopedics)
Paediatric calcaneal fractures are rare injuries usually managed conservatively or with open reduction and internal fixation (ORIF). Closed reduction was previously thought to be impossible, and very few cases are reported in the literature. We report a new technique for closed reduction using Ilizarov half-rings. We report successful closed reduction and screwless fixation of an extra-articular calcaneal fracture dislocation in a 7-year-old boy. Reduction was achieved using two Ilizarov half-ring frames arranged perpendicular to each other, enabling simultaneous application of longitudinal and rotational traction. Anatomical reduction was achieved with restored angles of Bohler and Gissane. Two K-wires were the definitive fixation. Bony union with good functional outcome and minimal pain was achieved at eight-weeks follow up. ORIF of calcaneal fractures provides good functional outcome but is associated with high rates of malunion and postoperative pain. Preservation of the unique soft tissue envelope surrounding the calcaneus reduces the risk of infection. Closed reduction prevents distortion of these tissues and may lead to faster healing and mobilisation. Closed reduction and screwless fixation of paediatric calcaneal fractures is an achievable management option. Our technique has preserved the soft tissue envelope surrounding the calcaneus, has avoided retained metalwork related complications, and has resulted in a good functional outcome.